On the thermal behaviour of gas turbine filament seals - Pelegrin-Garcia, JD (2017)
Advanced rotating shaft seals have the potential to significantly increase the efficiency and performance of steam and gas turbines. Two such seals, brush and leaf seals, rely on the use of thousands of flexible filaments to close clearances between rotating components and their static casings. The current life of the components is poor compared to the rest of the gas turbine, limiting the seals’ deployment, particularly in the jet engine at high temperature and pressure. Poor understanding of the seal installation response to frictional heat generated at the point of filament-rotor contact during operation has limited the ability to predict engine closures and hence seal behaviour and life. The resulting temperature rises may compromise the mechanical integrity of the engine rotor in extremis leading to a shaft failure. This thesis considers the heat transfer mechanisms that govern frictional heating, of both the fluid and solid components in the vicinity of such seals, characterising the process both experimentally and using numerical models. Through the identification of key features of the heat transfer a simple numerical methodology is shown to predict the thermal behaviour of the seal installation sufficiently accurately for engine design purposes. A low order heat transfer model, using a simple electrical analogy for heat transfer is used to investigate frictional heat generation. When contact occurs between the rotor surface and the seal filaments, mechanical energy is dissipated as heat at the interface. This is conducted into the rotor and the seal filaments in proportions that depend on the heat transfer characteristics of both contacting bodies (thermal resistances). To calculate the heat partition ratio and the resulting contact temperature, the thermal resistances of both rotor and seal need to be known. To that end, a new test facility, the Seal Static Thermal Test Facility (SSTTF), is developed. This is first used to study the convective heat transfer occurring in the vicinity of the seal; heat transfer coefficients based on appropriate, scalable, gas reference temperatures are reported. Importantly the results show a larger area on the rotor surface affected by the presence of the seal than was assumed by previous workers. The test rig is further modified to generate heating in a static test rig equivalent to the frictional heating at the filament tips. The test rig allows the contact temperature between rotor and seal, a critical previously unknown parameter to be measured in a well-conditioned environment. The presence of many thousands of vanishingly small flow passages in filament seals makes their explicit modelling unfeasible for engine design purposes. Thus the results from the experimental campaign are used to develop a simple computational fluid dynamic model of the seal, including empirically derived frictional heating, and seal porosity models, to achieve similar leakage and surface heat transfer to the rotor as was seen in the static experiments. The low order CFD methodology presented in the thesis is finally employed to model the transient operation of a brush seal under engine representative rotor surface speeds and differential pressures. Experimental data were generated in the Oxford Engine Seal Test Facility for a typical brush seal rubbing against a high growth rotor. These experiments were modelled using CFD and finite element analysis using parameters derived from static tests for the porous modelling of the seal leakage. Comparison of results shows that, without further tuning, the thermal behaviour is captured well with a moderate conservative overestimation of rotor heating with increased differential pressure across the seal allowing the strategy to be used as an engine design tool.